Women perception of SARS-CoV-2 vaccination during pregnancy and subsequent maternal anxiety: a prospective observational study. (12th December 2022) - Mappa, Ilenia; Luviso, Maria; Distefano, Flavia Adalgisa; Carbone, Luigi; Maruotti, Giuseppe Maria; Rizzo, Giuseppe
Abstract: Objective: The use of Coronavirus 2 (SARS-CoV-2) vaccine in pregnant women is controversial and still not performed in Italy. Our objective was to evaluate the propensity of a population of Italian women to receive the vaccine and its psychological impact. Methods: A prospective, observational study was performed on pregnant women attending Ospedale Cristo Re Università Roma TorVergata. A multi-section questionnaire was sent to each included woman on the first day of available SARS-CoV-2 vaccination. Part-A was finalized to acquire maternal characteristics and to test the women's perception of vaccinations in pregnancy and their fear-induced by vaccines. Part-B included the State-Trait-Anxiety-Inventory (STAI) a validated test for scoring trait anxiety (basal anxiety, STAI-T) and state anxiety (STAI-S). An abnormal value of STAI was considered when ≥40. Comparisons of maternal variables were performed according to their vaccine attitude. Results: The questionnaire was completed by 161 women (80.5% of the population considered). A positive attitude toward the vaccine was present in 136 (84.5%) women (positive) while the remaining 25.5% considered the vaccine not useful (negative). Among the former group 52.9% were favorable to obtain the vaccine during pregnancy despite the current national limitations, a percentage significantly higher ( p = .02) than in the negative groups. Women with a negative attitude to the vaccine had a lower educational ( p = .002) and employment level ( p = .016) when compared to the positive group. In all the women a significant increase of STAI-S from STAI-T values was evidenced ( p < .0001). The incidence of abnormal STAI T values (basal anxiety) was similar between the 2 groups ( p = .81), while there was a significant increase of STAI-S values in the negative group (negative 88.0%; vs positive 63.4%; p = .018) Conclusions: The majority of pregnant women considered have a positive attitude to SARS-CoV-2 vaccine. Vaccine campaign seems to increase the maternal level of anxiety and this increase is more marked with a negative attitude toward the vaccine.